Actuation and design innovations in earthworm-inspired soft robots: A review - Liu, Jianbin; Li, Pengcheng; Zuo, Siyang (Frontiers in Bioengineering and Biotechnology, 2023)
Currently, soft robotics technologies are creating the means of robotic abilities and are required for the development of biomimetic robotics. In recent years, earthworm-inspired soft robot has garnered increasing attention as a major branch of bionic robots. The major studies on earthworm-inspired soft robots focuses on the deformation of the earthworm body segment. Consequently, various actuation methods have been proposed to conduct the expansion and contraction of the robot’s segments for locomotion simulation. This review article aims to act as a reference guide for researchers interested in the field of earthworm-inspired soft robot, and to present the current state of research, summarize current design innovations, compare the advantages and disadvantages of different actuation methods with the purpose of inspiring future innovative orientations for researchers. Herein, earthworm-inspired soft robots are classified into single- and multi-segment types, and the characteristics of various actuation methods are introduced and compared according to the number of matching segments. Moreover, various promising application instances of the different actuation methods are detailed along with their main features. Finally, motion performances of the robots are compared by two normalized metrics-speed compared by body length and speed compared by body diameter, and future developments in this research direction are presented.